Rivaroxaban and apixaban for the treatment of suspected or confirmed heparin‐induced thrombocytopenia. (26th October 2021) - Cirbus, Kristen; Simone, Pamela; Austin Szwak, Jennifer
ABSTRACT: What is known and objective: Heparin‐induced thrombocytopenia (HIT) is an adverse hematologic drug reaction that results in thrombocytopenia. This potentially life‐threatening event is due to the administration of heparin products, such as unfractionated heparin (UFH) and low‐molecular‐weight heparin (LMWH). The incidence of HIT occurs in <0.1%–7% of hospitalized patients treated with heparin products, with a risk of thrombosis as high as 50%. In 2018, the American Society of Hematology (ASH) recommended the utilization of direct oral anticoagulants (DOACs) in clinically stable patients at average bleeding risk with HIT. The objective of this study was to evaluate the prescribing patterns of rivaroxaban and apixaban for the treatment of suspected or confirmed HIT. Methods: This was a retrospective chart review from January 2013 through October 2019 at the University of Chicago Medicine. Twelve patients were identified to have received a DOAC for suspected or confirmed HIT. Results: Rivaroxaban was utilized in seven (58%) patients, six of whom received argatroban prior to starting rivaroxaban. Five (71%) of these patients were started on the recommended dose of rivaroxaban for VTE. Apixaban was utilized in five (42%) patients; four patients were started on argatroban and transitioned to apixaban. One patient was started on the suggested dose of apixaban for VTE. What is new and conclusion: After starting DOACs for suspected HIT, no patients had new thrombosis during hospitalization. Eight patients (67%) followed up at our institution within 6 months of their discharge date. No subsequent thrombi formation were identified for any of these patients. The results of this study add to the expanding literature regarding the safety and efficacy of DOAC use in HIT, and indicate DOACs are being increasingly utilized for the treatment of confirmed or suspected HIT. Abstract : Heparin‐induced thrombocytopenia (HIT) is an adverse hematologic drug reaction that results in thrombocytopenia. The 2018 American Society of Hematology guidelines introduce the use of direct oral anticoagulants (DOACs) in clinically stable patients at average bleeding risk with suspected or confirmed HIT. Rivaroxaban and apixaban were successfully utilized in twelve patients in our study, with no new occurrence of thrombosis during hospitalization.